Decreased basic metabolic rate may reflect pituitary secretion disturbance in elite female athlete - Lagowska, K.; Kapczuk, K.; Jeszka, J.; Friebe, Z. (Science & Sports, 2014)
Aim: To evaluate the relationship between basal metabolic rate, energy balance and hormones level in young female athletes with menstrual disorders. Materials and methods: Thirty-three well-trained young female athletes, aged 18.4 ± 2.9 years, with menstrual disorders due to hypothalamic-pituitary dysfunction, participated in the study. Evaluation of nutritional status was based on analyses of body composition using the BIA method (fat mass [FM], fat-free mass [FFM]). Basal metabolic rate (BMR) was assessed with a portable indirect calorimeter. Serum luteinizing hormone (LH), folliculate-stimulating hormone (FSH), estradiol (E2), TSH, testosterone (T), prolactin (PRL) and sex-hormone binding globulin (SHBG) and leptin levels were measured. Total energy expenditure (TEE) was evaluated using the HR-Flex method. Dietary records for 7 consecutive days were used to evaluate the athletes` energy and nutrient intakes. Results: Depending on the measured BMR value and comparing with the Harris-Benedict equation, female athletes were assigned to one of the two groups: LBMR group with low BMRs and HBMR group with high BMRs. Serum leptin (P < 0.016) and LH levels (P < 0.003) were significantly lower in the LBMR group. In the LBMR athletes, a tendency towards negative energy balance was observed (P < 0.032). Significant correlations were found between BMR and LH level (P < 0.021) and between LH and leptin levels (P < 0.001) in the entire sample. Decreased BMR may reflect pituitary secretion disturbance in elite female athlete.